(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
This study was conducted to identify phytochemical constituents present in the methanolic root-bark extract of B. dalzielii using GC-MS analysis and conventional phytochemical evaluation. The studies revealed the presence of alkaloids, flavonoids, saponins, cardiac glycosides, terpenoids and carbohydrates. A total of forty three compounds composed of eighteen major components were identified thus; oxetane-2,3,4-trimethyl (3.45%), Bicyclo[4.1.0] heptan-3-one-7,7-dimethyl-4- methylene(IR) [2.69%], 2-methyl-2-(-2-oxopropyl) furan (3.20%), Cyclohexane, 2- (dimethylhydrazono)-3-[4-hexenyl]-1-acinitro,(E,) [2.63%], 3,8-Dihydroxy-3,4-dihydronaphthalen 1(2H)one (4.43%), 2-Tetradocanol (4.89%), 3-methyl-2-(2-oxopropyl)furan (3.46%), (2H)- Naphthalenenone, 6-(1,1-dimethyl ethyl) octahydro-2,8a-dimethyl (3.80%), Pentadecanoic acid (6.18%), undecanoic acid (3.68%), Phthalic acid (4.14%), 1-Allyl-cyclohexane-1,2-diol (3.95%), 1,5,9- cyclotetradecatriene, 1,5,9-trimethyl-12-(1-methyl ethyl) [4.58%], 9,12-octadecadienoic acid (Z,Z)- methyl ester (4.75%). 9-octadecenoic acid, methyl ester[E] (4.36%), Tetradecanoic acid-methyl ester(S) [3.90%], (2S,4R)-p-mentha-[1(7),8]-diene-2-hydroperoxide (2.62%) and 1-Naphthalenepropanol, α ethyldecahydro-8a-(hydroxymethyl)-α, 5-dimethyl-2-methylene (2.93%). Most of the identified compounds have been reported to possess various biological activities such as antimicrobial, anti inflammatory, antimalarial, antidiabetics, anti-asthmatic, anti-histamine, antitubercular, anti diarrhoeal among others. The studies thus concluded that B. dalzielii root-bark possesses potent bioactive compounds and is recommended as a plant of phytopharmaceutical importance. The presence of these bioactive compounds justifies the use of this plant in ethnomedicine.